Agricultural biotechnology in the courts: judicial opinions and commentary - Kershen, Drew L. (Frontiers in Bioengineering and Biotechnology, 2025)
Seven jurisdictions from around the world have issued judicial opinions that address fundamental issues about the governance and regulatory systems of agricultural biotechnology. This article summarizes these legal proceedings and describes their impact upon agricultural biotechnology. The article then provides a commentary and critique of the legal proceedings and resulting judicial opinions.